The Role of Communication Technology Toward Employee Performance - Isnaini Miryatil Jannah; Agung Dwi Nugroho (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This research aims to determine how important the role of communication technology on employee performance. This study uses a qualitative method with a descriptive approach. communication is needed in employee performance without communication, organizational goals will not be achieved, employee performance must be made as comfortable as possible so that employees can work with enthusiasm and can complete tasks. The influence of technology is very important nowadays because it is very rare that people today do not use technology to both communicate and provide related information. Motivating employee performance can make employees more enthusiastic at work.